Role of rehabilitation in chronic stress-induced exhaustion disorder: A narrative review - Johanna Wallensten; Marie Åsberg; Maria Wiklander; Anna Nager (Medical Journals Sweden, 2019)
Objective: An increase in numbers of cases of sick leave due to stress have been reported from several European countries during recent decades. Chronic stress-induced exhaustion disorder is associated with physiological and neurobiological perturbations that may contribute to cognitive problems and long-term exhaustion. Rehabilitation of patients with chronic stress-induced exhaustion disorder is therefore challenging. This narrative review summarizes the evidence regarding the effectiveness of different interventions for the rehabilitation of patients with chronic stress-induced exhaustion disorder. Methods: Both structured and unstructured searches of research studies and reports were performed in order to find knowledge sources. The structured search had 2 predefined inclusion criteria: (i) chronic stress-induced exhaustion/clinical burnout/severe burnout/stress-induced exhaustion; and (ii) rehabil-itation with improvement of symptoms and/or return to work as outcomes. Results: Cognitive behavioural interventions and multimodal interventions seem to reduce symptoms. Workplace interventions, either work-focused cognitive behavioural or workplace dialogue, seem to improve return to work. Sleep is important for both symptom improvement and return to work, and interventions for improving sleep might therefore be important. For improvement of cognitive function, which is a main complaint among patients with chronic stress-induced exhaustion disorder, aerobic and cognitive training may have some effect. Conclusion: In summary, the few studies of high-quality that examine interventions for rehabilitation of chronic stress-induced exhaustion disorder show only marginal effects. Thus, it is important to prevent the onset of chronic stress-induced exhaustion disorder.